1982
DOI: 10.1007/bf02141780
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal platelet aggregation response in Huntington's disease

Abstract: Platelet aggregation response to epinephrine, dopamine, serotonin, adenosine diphosphate, arachidonic acid, and collagen was examined in seven patients with Huntington's disease and nine of their relatives. All patients, except for two cases that were in terminal states, showed enhanced response to all the stimulants, especially to dopamine and epinephrine. The platelet aggregation response in many relatives also deviated from the normal limit. The relationship between platelet aggregation abnormality in Hunti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In light of these contradictory findings, we further performed tail bleeding tests in HD mice to evaluate whether thrombosis was indeed affected. Results showed that manifest R6/2 mice bleed less and for shorter periods of time, suggesting that platelets are hyperfunctional and may more readily promote thrombosis, in agreement with the findings described above 47. However, assessment of the cytoarchitecture of blood vessels in the tail of R6/2 mice of the same age (late-stage disease) further revealed important modifications in the vascular network in comparison to WT mice which supports our previous findings of such abnormalities within cerebral tissue 4.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In light of these contradictory findings, we further performed tail bleeding tests in HD mice to evaluate whether thrombosis was indeed affected. Results showed that manifest R6/2 mice bleed less and for shorter periods of time, suggesting that platelets are hyperfunctional and may more readily promote thrombosis, in agreement with the findings described above 47. However, assessment of the cytoarchitecture of blood vessels in the tail of R6/2 mice of the same age (late-stage disease) further revealed important modifications in the vascular network in comparison to WT mice which supports our previous findings of such abnormalities within cerebral tissue 4.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, one publication from the 1980s demonstrated that low levels of serotonin can be released from platelets in HD and that the aggregation process of platelets is seemingly impaired 35. Two publications followed up on this and one showed that platelet serotonin levels did not vary in HD,31 while the other demonstrated that platelets were more responsive and therefore aggregated more easily 47. Some antidepressants, such as selective serotonin reuptake inhibitors (SSRI), are responsible for the uptake of serotonin into platelets.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously described an altered homeostasis of human platelets in HD [25], [26] and an increased density of Adenosine A2a receptor, a protein G-coupled receptor implicated in the regulation of different biochemical processes including the release of NO, in both CNS of transgenic HD mice [13], [27] and blood platelets of patients [5], [6]. However, whether platelets dysfunction contributes to HD pathogenesis, or is an epiphenomenon, remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging aspects in neurodegenerative processes have been indeed identified at the crossroad between redox homeostasis, tryptophan metabolism as well as inflammation paths and mitochondrial function (Sas et al, 2007;Shukla et al, 2011). Noteworthy, an increased platelet responsiveness to aggregation stimuli was observed in symptomatic patients (Muramatsu et al, 1970) together a blunted NO release in advanced HD (Carrizzo et al, 2014). It seems therefore plausible to assume that platelets change their reactivity in HD, showing BDNF contents that fluctuate dynamically as a function of the progression of the disease and/or administered treatments.…”
Section: Discussionmentioning
confidence: 99%